Environmental Engineering, Fourth Edition - Matthews, Robin (Butterworth-Heinemann, 2012)
The text presents the engineering principles governing the generation and control of air and water pollutants, solid and hazardous waste, and noise. Water quality and drinking water treatment are discussed, as well as the elements of risk analysis.